Fracture Effectiveness Evaluation of Ultra-Deep Tight Sandstone Reservoirs: A Case Study of the Keshen Gas Field, Tarim Basin, West China - Wang, Zhimin; Xu, Ke; Zhang, Hui; Wang, Haiying; Yin, Guoqing; Wang, Zhaohui; Zhao, Wei (Frontiers in Earth Science, 2022)
Fracture effectiveness evaluation has an important impact on the efficient exploration and development of ultra-deep fractured reservoirs. Based on the liquid production profile results collected during the development of the Keshen gas field and based on the traditional static evaluation of fracture density, opening and filling degree, the fracture effectiveness evaluation of ultra-deep reservoirs is carried out from the perspectives of fracture activity, fracture opening and fracture connectivity. The results show that the static characteristics, such as fracture density and fracture properties, are only some factors that determine the effectiveness of fractures. From the perspective of contributions to reservoir permeability, dynamic parameters such as fracture activity, fracture opening and fracture connectivity are the key factors in determining the effectiveness of fractures. Practice has proven that fractures with a high shear ratio, low stress environment and high connection with the fracture system around the well are the main seepage channels for oil and gas supply in the development process. The research results provide a scientific basis for well location deployment, optimization of reconstruction intervals and optimization of development schemes.